Fair trade: Tightening up the chain - Lightfoot, Clive (Technical Centre for Agricultural and Rural Cooperation, 2008)
Using the internet and mobile phones, farmers in East Africa learn to work more effi ciently with the traders who buy their goods. The Linking Local Learners method of learning explores how farmers can access market information and get a fairer deal.